Multi-Level Leadership Development Using Co-Constructed Spaces with Schools: A Ten-Year Journey - Howard Youngs; Maggie Ogram (MDPI AG, 2024)
Leadership in both theory and practice usually emphasizes a person and a position. There has been a shift from emphasizing the senior level of organizational roles, to include the middle level and other sources of leadership. Nomenclature has emerged over time to reflect this, for example, collective, distributed, shared, and collaborative leadership. Another understanding of leadership needs to be added, one that does not first emphasize a person or position, instead incorporating process and practices, weaving through all levels and sources of leadership. This additional understanding has implications for how leadership development is constructed and facilitated. Over the last ten years, the authors have journeyed with groups of schools, using an emerging co-constructed approach to leadership development. The journey is relayed across three seasons. The first is the grounding of collaborative practices through inquiry, informed by a two-phase research project. The second focuses on adaptation and resilience during the COVID-19 pandemic, whereas the third delves deeper into what sits behind prevalent practices that may enable and hinder student achievement. Our narrative over time shows that leadership development can be shaped through a continual cycle of review, reflection, and co-construction, leading to conditions for transformation across multiple levels and sources of leadership.